Internalizing Semar’s values in the development of counselor identity: A systematic literature review - Putra Wibisono; M. Ramli; Fitri Wahyuni (Academic Journal of Psychology and Counseling, 2026)
Recent discussions on counselor development in Indonesia have highlighted the importance of cultural foundations in professional identity formation. However, systematic studies examining local wisdom, particularly the values embodied by Semar, remain limited. This study aimed to explore how Semar’s philosophical values can be internalized in counselors’ self-development and contribute to strengthening guidance and counseling (GC) services. Using a systematic literature review (SLR) with the PRISMA framework, this study analyzed articles obtained from Scopus, Publish or Perish, ResearchGate, and Google Scholar. Of the 84 identified articles, thirteen met the inclusion criteria based on relevance and quality. The findings indicate that Semar’s values—such as wisdom, empathy, sincerity, humility, emotion regulation, and dedication—provide a meaningful foundation for counselor character development. Integrating these values into counselor education and practice may enhance ethical awareness, cultural sensitivity, and humanistic counseling services, contributing to more holistic and culturally grounded counselor development models.